Study on Efficacy of Nalbuphine Hydrochloride as Pre-Emptive Analgesic Comparison With Diclofenac Sodium after Open Cholecystectomy (Journal of the Bangladesh Society of Anaesthesiologists, 2009)
Preemptive analgesia is an antinociceptive treatment that prevents establishment of altered central processing of afferent input from sites of injury. The aim of this study was to evaluate the effects of preemptively used nalbuphine and diclofenac on postoperative pain and opioid consumption. Seventy five patients scheduled for open cholecystectomy were investigated by randomized study. Patients were divided into three groups. In group I, patients received Inj. Nalbuphine Hydrochloride (0.3 mg/kg bw IV) before induction. In group II, patients received Inj. Diclofenac Sodium (1 mg/kg bw IV) before induction and in group III patients received placebo before induction. General Anesthesia was given in all groups with Inj. Thiopental sodium 5mg/kg and Inj. Succninylcholine 1.5mg/kg to facilitate endotracheal intubation. Anesthesia was maintained with halothane 0.5% and nitrous oxide 66% in oxygen. Muscle relaxation was maintained by Inj.Vecuronium 0.1 mg/kg. Intraoperative proper hydration was maintained by lactate ringer's solution.In post operative period patients in all three groups received Inj. Pethidine 10mg IV till the patients got relieved from pain. The minimum interval of giving pethidine was 10 minutes. Through our study we have found that, pethidine consumption in 24 hours in group-I (Nalbuphine group) was 54.00±1.0, in group-II (Diclofenac group) was 74.00±1.0 and in group-III (Placebo group) was 112.0±2.0 and p-value